Animated Video Media with Contextual Approach on Social Science Subject in Fourth Grade Elementary School - Ningsih, Ni Putu Ayu; Astawan, I Gede; Rati, Ni Wayan (International Journal of Elementary Education, 2022)
Students do not concentrate and are bored when learning social science, so students' lack of enthusiasm in participating in learning activities impacts low social science learning outcomes. This research aims to develop an animated video with a contextual approach to the social science content theme 7, the beauty of my country's diversity for 4th-grade elementary school students. This type of research is the development of the ADDIE model. The research subjects are 2 media experts in the field of study and 2 learning media experts. The subjects of the research trial were expert practitioners and 10 4th grade elementary school students. The methods of collecting data are through observation, interview methods, and methods of distributing questionnaires. The data collection instrument was carried out by distributing questionnaires (questionnaires). The data analysis techniques are descriptive, qualitative, and quantitative. The study results are the assessments given by media experts for learning materials, 4.83. The results of the validity test of learning media experts obtained a score of 4.71. The average score in that range is included in the very good category (Valid). Based on the response test results, the practitioner obtained a score of 4.79 (very good), and the student was 4.38 (very good). Therefore, the animated video media with a contextual approach to the beauty of my country's diversity is declared valid. It is concluded that the Contextual approach to animation video is feasible to use in learning.